Analisis Sentimen Pandangan Masyarakat Terhadap Uji Emisi di Twitter Menggunakan Metode Support Vector Machine - Aziz Musthafa; Dihin Muriyatmoko; Anggi Fauzan (Prosiding SISFOTEK, 2024)
Air pollution caused by motor vehicles is a major problem today. To reduce the dangers of air pollution and pollution caused by increasing motor vehicle users, the government immediately enacted legal action against vehicles that did not conduct or pass emission tests. From these government actions there are various kinds of public opinions, especially on social media twitter. This study aims to classify public sentiment towards emission tests expressed on twitter social media by collecting comment data and labeling it as positive, negative, and neutral. The method used in this research with data amounting to 3459 comments uses Support Vector Machine (SVM). Meanwhile, to measure the performance of the SVM method using Confusion Matrix. The results of testing using the SVM method resulted in an accuracy of 76%, and the results of the classification obtained more positive class values. This states that the policies made by the government related to emission testing have received a positive response from the public.